Relationship between lumbar-pelvic alignment and uterine dimensions in dysmenorrhic girls - Randa Gomaa Mohamed Attia; Salwa Mostafa El-Badry; Amel Mohamed Yousef; Mohamed Hassan Mostafa; Hamada Ahmed Hamada (2024)
Background: Primary dysmenorrhea (PD) is characterized by severe abdominal cramps impacting daily life, especially among adolescents. Musculoskeletal factors, like pelvic and lumbar alignment, are suspected contributors. Uterine shape and cervix dimensions may also influence PD severity. Understanding these links is crucial for managing this condition effectively. Purpose: to provide an evidence base for the relationship between lumbar-pelvic alignment and uterine position in dysmenorrhic girls. Methods: This study included 40 girls with regular menstrual cycles, divided into two groups: 20 with PD (study group) and 20 with no pain during menstruation (control group). Spinopelvic alignment parameters, including thoracic kyphosis, lumbar lordosis, pelvic tilt, and pelvic torsion, were assessed using a three-dimensional Raster-stereography Formetric II system. Uterine dimensions, including corpus length and width, as well as cervix length and width, were measured by a high-resolution four-dimensional ultrasound device. Results: No significant correlations were identified between the spinopelvic alignment and uterine dimensions (p>0.05) in the study group with PD. Conversely, significant moderate negative correlations were observed between uterine corpus width and thoracic kyphotic angle (p<0.05), as well as between cervix length and pelvic tilt (p<0.05) in the control group without PD. Conclusion: In dysmenorrheic girls, there are no significant correlations between spinopelvic alignment and uterine dimensions. In contrast, in girls without dysmenorrhea, there are significant correlations between uterine corpus width and thoracic kyphotic angle, and between cervix length and pelvic tilt.
(3GdNdajI GdYdejI(B: (3jJejR YSQ GdWeK GdChdj HJbdUGJ TOjOI aj GdHWf JDKQ Ydi GdMjGI GdjhejI, hNGUI Hjf GdeQGgbGJ(B. (3jTJHg Cf GdYhGed GdYVdjI GdgjcdjI, eKd eMGPGI GdMhV hGdabQGJ GdbWfjI hTcd GdQMe hCHYGO Yfb GdQMe ef GdYhGed GdeDKQI Ydi TOI YSQ GdWeK GdChdj(B. (3jYO age gPg GdQhGHW CekQG HGdZ GdCgejI dYdGL gPg GdMGdI HTcd aYGd(B. (3GdgOa(B: (3JhajQ bGYOI COdI ddYdGbI Hjf eMGPGI GdMhV hGdabQGJ GdbWfjI hhVY GdQMe dOi GdaJjGJ GdeUGHGJ HYSQ GdWeK(B. (3WQb GdHMK(B: (3TGQcJ aj gPg GdOQGSI CQHYhf aJGI PGJ OhQGJ TgQjI efJXeI(B. (3hJe JbSjegf Edi eLehYJjf eJSGhjJjf(B. (3JCdaJ eLehYI GdOQGSI ef YTQjf aJGI dOjgf OhQI TgQjI efJXeI eY GdBe YSQ GdWeK GdChdj hJchfJ GdeLehYI GdVGHWI ef YTQjf aJGI dOjgf OhQI TgQjI efJXeI hdG JYGfjf ef Cj CdGe CKfGA GdMjV(B. (3hbO Je bjGS RGhjI GdJMOH GdUOQj hRGhjI GdGfMfGA GdbWfj hejd GdMhV hGdJhGA GdMhV HGSJNOGe GdJMdjd KdGKj GdGHYGO dLgGR GdahQeJQc, ceG Je bjGS CHYGO GdQMe HeG aj Pdc Whd hYQV LSe GdQMe hWhd hYQV Yfb GdQMe HGSJNOGe LgGR GdehLGJ ahb GdUhJjI QHGYj GdCHYGO YGdj GdObI(B. (3GdfJGFL(B: (3CXgQJ GdfJGFL YOe hLhO GQJHGWGJ PGJ OdGdI EMUGFjI Hjf eMGPGI GdYehO GdabGQj hGdMhV hCHYGO GdQMe aj eLehYI GdOQGSI (B((3GdEfGK GdeUGHGJ HYSQ GdWeK(B). (3Ydi GdYcS ef Pdc, dhMX hLhO GQJHGWGJ SdHjI eJhSWI PGJ OdGdI EMUGFjI Hjf YQV LSe GdQMe hRGhjI GdJMOH GdUOQj, hcPdc Hjf Whd Yfb GdQMe hejd GdMhV aj GdeLehYI GdVGHWI (B((3GdEfGK GddGJj dG JYGfjf ef YSQ GdWeK(B). (3GdNdGUI(B: (3dG JhLO YdGbI PGJ OdGdI EMUGFjI Hjf eMGPGI GdYehO GdabGQj hCHYGO GdQMe aj GdEfGK GdeUGHGJ HYSQ GdWeK(B. (3hYdi GdfbjV ef Pdc, JhLO GQJHGWGJ PGJ OdGdI EMUGFjI Hjf YQV LSe GdQMe hRGhjI GdJMOH GdUOQj, hHjf Whd Yfb GdQMe hEeGdI GdMhV aj GdaJjGJ ZjQ GdeUGHGJ HYSQ GdWeK(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 87-101.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Physical Therapy; dysmenorrhea -- lumbar -- alignment -- uterine position